Straight to Jesus : Sexual and Christian Conversions in the Ex-Gay Movement. - Erzen, Tanya (University of California Press, 2006)
Focuses on the everyday lives of men and women at New Hope Ministry, a residential ex-gay program. This study traces the stories of people who have renounced long-term relationships and moved from other countries out of a conviction that the conservative Christian beliefs of their upbringing and their own same-sex desires are irreconcilable.